Oil Active Fractions of Nigella Sativa and Their Activity Against Brest Cancer Cell Line MCF-7 - Taif H. Al-Ameedy (Journal of Global Pharma Technology, 2016)
Objective: Seeds of Nigella sativa have been used as spice and food preservative, also these seeds have been used to promote health and fight disease especially in the Middle East. The aime of this study is to evaluate the effect of partially purified oil fractions extracted from Nigella sativa purified oil fractions against breast cancer cell line. Methods: The oil of black seed was extracted with 96% ethanol and partially purified by adsorption chromatographically using silica gel column with different solvents depending on the polarity of N.sativa compositions. Subsequently the resulted fractions (hexne, chloroform, ethyl acetate, acetone, ethanol, methanol and water fractions) were tested as anticancer against breast cancer cell line Michigan cancer foundation-7 (MCF-7)  and compare with the human hepatic cell lineWRL 68 as a normal cell line. Results: The most effective oil fraction for killing MCF-7 cell  was hexane with IC5087.52µg/ml, followed ethyl acetate and ethanol fraction the cytotoxicity against WRL68 were  significantly (P≤ 0.0001) less than for MCF7 and it was 203.1µg/ml and 218.3µg/ml respectively. Whereas the rest fractions including chloroform, acetone, methanol and water fractions had slightly anticancer activity. Conclusion: The black seed oil contain effective compounds act as antitumor agents and their were had no activity against normal cell, so we can use a chemotherapy drugs after perform another detailed research for other activities and study the chamical structure to modify for increase their anticancer activity. Keywords: Nigella sativa, Oil seeds, Anticancer activity, Medicinal plants.